Pengaruh Kepemimpinan dan Kompetensi Karyawan terhadap Komitmen Organisasi PT Populer Kaca Utama - Ferry Felixius; Ika Suhartanti Darmo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The number of employees with a low level of organizational commitment can raise a new concern. The level of organizational commitment can be influenced by several factors, such as external (from outside) employees such as leaders in the company, and internal employees such as the competence of the employees themselves.This study aims to determine the effect of leadership and employee competence on organizational commitment at Pt. Popular Main Glass. This study uses a quantitative approach by distributing questionnaires to 60 field employees from Pt. Popular Main Glass. Researchers conducted tests based on several backgrounds and expert opinions and examined and concluded into several conclusions. In this study it was found that there is an influence of leadership and employee competence on organizational commitment. Therefore, the researcher's suggestion for Pt. Popular Glass Utama is to always pay attention to leadership factors and employee competence to get organizational commitment from employees.